2017
DOI: 10.12816/0039690
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Serum Ferritin Level in Preterm Labour

Abstract: Background: Preterm birth is the leading cause of newborn deaths and also the leading cause of death in children under 5 years of age. There is wide spread suspicion that subclinical infection is a common accompaniment and cause of preterm labour. Ferritin is an acute phase reactant and it increases during inflammation. Aim: The objective of this study is to measure serum ferritin level in cases of established preterm labour (PTL) as a possible marker of infection. Study Setting: This study conducted at Ain Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Besides, Khambalia et al revealed that high maternal ferritin level in the early time of pregnancy (12 weeks of gestation) was associated with an increased risk of preterm delivery (23). El-Shahawy et al also showed that ferritin level was significantly higher in the preterm group at 30-34 weeks than in uncomplicated pregnancies at the same age of gestation, and ferritin level above 55 ng/mL with a sensitivity of 96.7% and specificity of 96.7% could be used as a predictor of preterm delivery (15). Finally, Abdel-Malek et al showed that serum ferritin level at week 30 of gestation was significantly higher in the preterm group (76.3±29.4 ng/mL) than in the control group (20.2±5.0 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Khambalia et al revealed that high maternal ferritin level in the early time of pregnancy (12 weeks of gestation) was associated with an increased risk of preterm delivery (23). El-Shahawy et al also showed that ferritin level was significantly higher in the preterm group at 30-34 weeks than in uncomplicated pregnancies at the same age of gestation, and ferritin level above 55 ng/mL with a sensitivity of 96.7% and specificity of 96.7% could be used as a predictor of preterm delivery (15). Finally, Abdel-Malek et al showed that serum ferritin level at week 30 of gestation was significantly higher in the preterm group (76.3±29.4 ng/mL) than in the control group (20.2±5.0 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above studies, which determine a cutoff point for ferritin level for predicting preterm labor, several studies have addressed the predictive role of ferritin in preterm delivery (14,15,(21)(22)(23). Singh et al reported that ferritin was a better predicting biomarker for preterm delivery than other indicators (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings weren't coincides with Elnasr and Ammar, [13] who demonstrated that the AUC for s-ferritin is 0.97, the cutoff value 110.5 ng/ml with sensitivity 86.7%, Specificity 94.1% and 95% CI 0.94-1.0. Also, El-Shahawy et al, [14] conducted (ROC) curves which were constructed for s-ferritin as predictor of pre-term labor. Sferritin was a highly significant predictor of pre-term delivery and more than 55 ng/mL was the optimal cut-off point.…”
Section: Discussionmentioning
confidence: 99%
“…The time of viability varies the newborn (TTN), neonatal jaundice, respiratory distress syndrome (RDS), necrotizing enterocolitis (NEC), sepsis, and prolonged NICU stay. 1 Each year, 15 million preterm births are predicted to occur, with 1.1 million newborns dying as a result of preterm birth complications. Preterm birth prevention is the single most critical problem facing modern obstetrics today, yet progress has been limited by a lack of knowledge of the core mechanisms that cause early labour and delivery.…”
Section: Introductionmentioning
confidence: 99%